An assessment of tape-lifts. (July 2020) - Kanokwongnuwut, Piyamas; Paul Kirkbride, K.; Linacre, Adrian
Highlights: Fourteen types of tapes were assessed for latent DNA recovery and detection. Inhibition, autofluorescence and efficiency of collection was tested. Three tapes were suitable for latent DNA collection DD staining and direct PCR. Tape-lifting from touched fabrics using three tapes produced full DNA profiles. Abstract: Tape-lifting is a non-destructive alternative to swabbing for collection of biological materials deposited on surfaces, especially on porous substrates. While there have been a number of studies looking at the efficiency of tapes in terms of recovery and their effect on downstream processes, none has been able to visually monitor cellular material collection. We report on a comparative study of a range of tapes regarding their collection efficiency of cellular material visualised using fluorescence microscopy, their background fluorescence after staining with DD diluted with three different solvent types and inhibition of subsequent PCR using direct PCR. Three of the fourteen tapes were selected for further testing. These were brown packing tape (Packmate™), clear tape (Sellotape®), and DNA-free tape (Lovell Surgical Solutions). These did not inhibit direct STR amplification; the other eleven tapes exhibited either high background fluorescence and/or inhibition of subsequent PCR. The effectiveness of the three tapes for the collection of cellular material was tested after tape-lifting a fingermark once, twice and ten times. The amount of cellular material within fingermarks stained with Diamond™ dye (DD) was recorded using fluorescence microscopy before and after tape-liftings. The DNA-free tape (Lovell) used in many forensic laboratories gave poor recovery compared to the other two tapes. After a tape-lift, an average of 30 % of cellular material was recovered by using DNA-free tape (Lovell), contrasting with an average recovery of 59.5 % for the clear tape (Sellotape®) and 88.8 % for the brown packing tape (Packmate™). The results presented show that standard crime scene sampling tape does collect DNA but is less effective than shop-bought tapes. Full DNA profiles can be generated from all of touched fabric samples that were collected DNA using the three tapes, triaged by DD staining and amplified by direct PCR approach.